Transformações geométricas: um olhar matemático nos flocos de neve usando o origami e o GeoGebra - Chihaya, Mariana Candéa (2022)
The present work aims to study geometric transformations using snowflakes as a motivating element due to their characteristics and peculiarities. The study presents a brief history of the snowflake and its physicochemical conditions. Then, it explores the contents of geometric transformations present in different snowflake formats. It also develops didactic proposals for students in the 7th and 8th-grade of Elementary School, using the ancient Japanese technique of folding paper, origami, and cutting paper, kirigami, in addition to the mathematics software GeoGebra. Low-cost tools like paper and free software GeoGebra have the potential to help Elementary School teachers to awaken in students an interest in geometric transformations.